Shock wave lithotripsy: the new phoenix? - Neisius, Andreas; Rassweiler, Jens (World journal of urology, 2015)
Introduction: Following its introduction in 1980, shock wave lithotripsy (SWL) rapidly emerged as the first-line treatment for the majority of patients with urolithiasis. Millions of SWL therapies have since been performed worldwide, and nowadays, SWL still remains to be the least invasive therapy modality for urinary stones. During the last three decades, SWL technology has advanced in terms of shock wave generation, focusing, patient coupling and stone localization. The implementation of multifunctional lithotripters has made SWL available to urology departments worldwide. Indications for SWL have evolved as well. Although endoscopic treatment techniques have improved significantly and seem to take the lead in stone therapy in the western countries due to high stone-free rates, SWL continues to be considered as the first-line therapy for the treatment of most intra-renal stones and many ureteral stones. Methods: This paper reviews the fundamentals of SWL physics to facilitate a better understanding about how a lithotripter works and should be best utilized. Results: Advances in lithotripsy technology such as shock wave generation and focusing, advances in stone localization (imaging), different energy source concepts and coupling modalities are presented. Furthermore adjuncts to improve the efficacy of SWL including different treatment strategies are reviewed. Conclusion: If urologists make use of a more comprehensive understanding of the pathophysiology and physics of shock waves, much better results could be achieved in the future. This may lead to a renaissance and encourage SWL as first-line therapy for urolithiasis in times of rapid progress in endoscopic treatment modalities.